Why Do We Need Media Multitasking? A Self-Regulatory Perspective - Popławska, Agnieszka; Szumowska, Ewa; Kuś, Jakub (Frontiers in Psychology, 2021)
In the digital world of today, multitasking with media is inevitable. Research shows, for instance, that American youths spend on average 7.5 h every day with media, and 29% of that time is spent processing different forms of media simultaneously (Uncapher et al., 2017). Despite numerous studies, however, there is no consensus on whether media multitasking is effective or not. In the current paper, we review existing literature and propose that in order to ascertain whether media multitasking is effective, it is important to determine (1) which goal/s are used as a reference point (e.g., acquiring new knowledge, obtaining the highest number of points in a task, being active on social media); (2) whether a person's intentions and subjective feelings or objective performance are considered (e.g., simultaneous media use might feel productive, yet objective performance might deteriorate); and finally (3) whether the short- or long-term consequences of media multitasking are considered (e.g., media multitasking might help attain one's present goals yet be conducive to a cognitive strategy that leads to lesser attentional shielding of goals). Depending on these differentiations, media multitasking can be seen as both a strategic behavior undertaken to accomplish one's goals and as a self-regulatory failure. The article integrates various findings from the areas of cognitive psychology, psychology of motivation, and human-computer interaction.